Simulation of Bit Error Detection Method Using Hamming Code Web -Based (Dinamika Informatika, 2016)
The objective of the study is to design an applications of Simulation Bit Error Detection Using Hamming Code Method Web –Based. This study designs a simulation application that aims to portray how the process of correcting errors in the data transmission process in the form of numbers in binary numbers. The method used Hamming Code as a design of Simulation. Based on the test result, the data transmitted would be detected if an error occured, then the application would correct the errors that had been detected. Observations indicate that error occured during data transmission because of an error on the bits to be sent, then there was an error. The simulation can help in understanding more about how the process of sending data and the error correction.   Kata Kunci : Bit Error,  Hamming Code